Cooperative Learning with FIF Oral Training Application to Enhance Speaking Proficiency During Off-class Time and Interest towards Speaking English - He, Lanhua; Julian Robillos , Roderick (Forum for Linguistic Studies, 2025)
This study investigated the effectiveness of integrating cooperative learning with the FiF App to improve students'English-speaking proficiency during off-class hours. The study's overarching aim was to enhance speaking proficiency in semantics, pronunciation, fluency, and completeness, increase students'interest, and examine their learning experiences.The study employed a mixed-methods approach with a one-group pre-test and post-test design involving 49 Primary English Education students from Lijiang Normal University. The 9-week intervention involved cooperative learning-based lesson plans, and the FiF App. Speaking proficiency was assessed before and after the intervention through the app, while students'interest towards speaking English and experiences were measured using questionnaires and semi-structured interviews.Results showed significant improvement in overall speaking proficiency, with mean scores increasing from 49.57 to 69.96, t(48) = 6.16, p < 0.001. Pronunciation improved from 59.94 to 85.61 (t = -7.48, p < 0.001), and semantics increased from 29.55 to 53.55 (t = 5.59, p < 0.001). Although fluency scores decreased numerically from 78.98 to 64.31, the t-test (t = 4.41, p < 0.001) indicated significant improvement, likely to reflect greater accuracy over speed. Completeness rose slightly from 92.78 to 95.69 while moderate increases in speaking confidence (M = 3.23) and positive perceptions of cooperative learning (M = 3.86). The perceived importance of speaking skills was lower (M = 2.66). Interview data supported these findings, highlighting enhanced motivation, more meaningful peer interaction, and increased opportunities for practice. This study demonstrates the effective combination of cooperative learning and mobile-assisted oral training outside class, encouraging educators to adopt blended models to improve English-speaking proficiency beyond traditional classroom settings.